Complete mitochondrial genome and phylogenetic analysis of Gracilaria spinulosa. Issue 1 (2nd January 2019) - Wang, Shanshan; Zhang, Jing; Qian, Hao; Chen, Weizhou; Liu, Tao; Tang, Xianming
Abstract: In this study, the complete mitochondrial genome (mitogenome) of Gracilaria spinulosa was reported for the first time. The complete mitogenome was 25, 734 bp in length and contained 50 genes including 24 protein-coding, two rRNA, 23 tRNA genes, and one unidentified open reading frame (ORF). The structure of G. spinulosa mitogenome was similar to the other species in Gracilaria . The Bayesian phylogenetic analysis of Gracilariaceae revealed that G.spinulosa first clustered together with Gracilaria textorii, showing a distant relationship with Gracilaria chouae and Gracilaria vermiculophylla .